PKM PENDEKATAN MULTIDISIPLIN KEBERMANFAATAN KEBERLANJUTAN DI DESA CIPICUNG - Sasongko, Shevila Ghita; Nuraliyah, Siti; Lathifah SD , Fifit; Simbolon, Silviana; Kusuma, Jaka Wijaya; Sulaeman, Yeni (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The Student Creativity Program (PKM) with a multidisciplinary approach that focuses on usefulness and sustainability has been implemented in Cipicung Village as a form of community service. This activity aims to improve the welfare of the community through science-based innovations from various disciplines, including technology, economics, and socio-culture. The methods used include observation, training, and community assistance in developing sustainable local potential. The results of the activity show that there is an increase in community skills in the optimal use of village resources, an increase in income through economic empowerment programs, and awareness of environmentally friendly practices. With a holistic and sustainable approach, this program is expected to become a model of independent and innovative village development